CHINA'S FOREIGN POLICY TOWARDS THE UNITED ARAB EMIRATES THROUGH THE BELT AND ROAD INITIATIVE (BRI): Kebijakan Luar Negeri Cina Terhadap Uni Emirat Arab Melalui Belt ‎And Road Initiative (BRI)‎ - Pasaribu, Rachel Graceya Epipania Junissi; Sari, Deasy Silvya; Konety, Neneng (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2025)
China and the UAE have established close bilateral relations strengthened by the Belt and ‎Road Initiative (BRI) first launched by President Xi Jinping in 2013. With the BRI, China aims to ‎implement its foreign policy based on various factors, objectives, and alternative strategies ‎that can be implemented. Using the Analytical Hierarchy Process (AHP) method combined ‎with questionnaire and interview methods, the researcher aims to determine the increase in ‎bilateral cooperation and infrastructure development as part of China's foreign policy ‎orientation towards the UAE through the BRI. This study found that national security is the ‎main factor behind China's foreign policy, and infrastructure development is a priority goal in ‎the existing factors. The alternative strategy that is a priority is the development of energy ‎projects, which is also supported by China's ambition in developing energy infrastructure and ‎the UAE as an oil and gas producing country and its commitment to producing renewable ‎energy.‎